How are you coping? Stress, coping, burnout, and aggression in forensic mental healthcare workers - Spaan, Pascalle; van den Boogert, Frank; Bouman, Yvonne H. A.; Hoogendijk, Witte J. G.; Roza, Sabine J. (Frontiers in Psychology, 2024)
Introduction Perceived stress at work has been linked to several adverse outcomes in workers, including increased risk of burnout and aggression (e.g., anger and irritability). However, much remains unknown about factors that might mitigate the negative influences of perceived stress on workers’ well-being. This study focusses on coping as a possible protective factor against perceived stress and its consequences in forensic mental healthcare workers. We aimed to identify which higher-order coping factors were present in this worker sample and to investigate whether these coping factors modify the associations between perceived stress and burnout or aggression. Methods For this observational survey study, 116 forensic mental healthcare workers completed questionnaires assessing changes in work situation since the start of COVID-19, perceived stress, coping, burnout symptoms, and aggression. Results Results from principal component analysis indicated that four higher-order coping factors could be distinguished: social support and emotional coping, positive cognitive restructuring, problem-focused coping, and passive coping. Higher perceived stress levels were associated with higher levels of both burnout and aggression in workers. Problem-focused coping was associated with less burnout symptoms in workers. Furthermore, positive cognitive restructuring was associated with less aggression in workers. Discussion In conclusion, problem-focused coping and positive cognitive restructuring may protect workers against burnout symptoms and aggression and these results may inform future studies on preventive interventions aimed at promoting worker’s well-being.